Arachidonic Acid-Dependent Pathway Inhibition in Platelets: its Role in Multiple Injury-Induced Coagulopathy and the Potential Mechanisms. Issue 1 (January 2021) - Tang, Yao; Huang, Sunhua; Lin, Wenhao; Wen, Ke; Lin, Zhexuan; Han, Ming
ABSTRACT: Background: Our previous study demonstrated the types of platelet dysfunction varied at early stage (∼3 h) in trauma-induced coagulopathy (TIC) caused by different types of injuries. And arachidonic acid (AA)-dependent pathway inhibition in platelet seemed to be specific for TIC caused by multiple injury (MI). The aim of this research was to further study AA-dependent pathway inhibition in platelets in a rat model of TIC caused by MI and to explore its potential mechanisms. Methods: Sprague-Dawley rat model of TIC caused by MI was established. We used thrombelastography with platelet mapping as a measure of platelet function to assess the inhibitory extent of AA-dependent activation pathway. Flow cytometry was used to determine the expression of activation-dependent granular protein P-selectin (CD62P). In addition, the plasma levels of 6-Keto-prostaglandin F1 alpha (6-Keto-PGF1α ), Prostaglandin E2, and Thromboxane B2 were assessed by enzyme-linked immuno sorbent assay. Results: The inhibition rate of AA-dependent pathway after injury was significantly higher than that of control. The maximum amplitude decreased in the MI group, compared with that of control. The percentage of CD62P expression in the MI group was remarkably lower than that of control after AA treatment. The plasma concentrations of 6-Keto-PGF1α and PGE2 increased in the MI group. Conclusion: Platelets inhibition was observed in TIC caused by MI at early stage after injury, which might be partially attributed to AA-dependent activation pathway dysfunction. The increase of plasma Prostacyclin and PGE2 levels may contribute to the inhibition process.